Are migraine and non‐migrainous headache risk factors for stroke in the elderly? Findings from a 12‐year cohort follow‐up. (11th July 2016) - Norton, J.; Portet, F.; Gabelle, A.; Debette, S.; Ritchie, K.; Touchon, J.; Berr, C.
Abstract : Background and purpose: There is evidence that migraine is a risk factor for stroke but little is known about this association in elderly people. Furthermore, non‐migrainous headache (NMH) has received little attention despite being the most frequently reported type of headache. Late‐life migraine and NMH were examined as candidate risk factors for stroke in a community‐dwelling elderly sample over a 12‐year follow‐up. Methods: One thousand nine hundred and nineteen non‐institutionalized subjects aged 65+, without dementia (Diagnostic and Statistical Manual of Mental Disorders, 4th edition, DSM‐IV criteria) and with no stroke history at baseline, were drawn from the Three‐City Montpellier cohort (recruitment 1999–2001) for longitudinal analysis. Ischaemic and haemorrhagic stroke was reported at baseline and at each of the five follow‐ups, with cases validated by a panel of experts, according to ICD‐10 criteria (International Classification of Diseases, 10th revision). Migraine and NMH were determined at baseline during a neurological interview and examination using 1988 International Headache Society criteria. Results: A total of 110 (5.4%) cases of migraine and 179 (8.9%) cases of NMH were identified at baseline. During the median 8.8‐year follow‐up, incident stroke was observed in 1.9% of baseline migrainers, 6.2% of NMH and 3.6% of those with no lifetime history of headache. Cox proportional hazard models indicated that migraine was not a risk factor for stroke; however, NMH sufferers were twice as likely to have a stroke (hazard ratio 2.00, 95% confidence interval 1.00–3.93, P = 0.049). Conclusions: This study is one of the first to suggest that late‐life NMH rather than migraine could be an independent risk factor for stroke and a warning sign. The incidence of stroke in elderly migrainers, seldom reported, is particularly low.